2004
DOI: 10.1074/jbc.m401761200
|View full text |Cite
|
Sign up to set email alerts
|

Group I Metabotropic Glutamate Receptors Mediate a Dual Role of Glutamate in T Cell Activation

Abstract: Metabotropic glutamate receptors (mGluR) are present in cells of the nervous system, where they are activated by one of the main neurotransmitters, glutamate. They are also expressed in cells outside the nervous system. We identified and characterized two receptors belonging to group I mGluR, mGlu1R and mGlu5R, in human cell lines of lymphoid origin and in resting and activated lymphocytes from human peripheral blood. Both are highly expressed in the human Jurkat T cell line, whereas mGlu5R is expressed only i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
126
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 124 publications
(132 citation statements)
references
References 21 publications
4
126
0
Order By: Relevance
“…Traditionally, it has been thought that the functions of immune cells such as T cells and DCs are regulated mainly by cytokines. However, a number of more recent studies have shown that immune system cells can also be regulated by neurotransmitters (6)(7)(8)(9)(10)(11). Consistent with this, both primary and secondary lymphoid organs are highly innervated by sympathetic ends that store dopamine (DA) (12,13).…”
Section: Endritic Cells (Dcs) Are the Most Efficient Type Of Apcsmentioning
confidence: 88%
“…Traditionally, it has been thought that the functions of immune cells such as T cells and DCs are regulated mainly by cytokines. However, a number of more recent studies have shown that immune system cells can also be regulated by neurotransmitters (6)(7)(8)(9)(10)(11). Consistent with this, both primary and secondary lymphoid organs are highly innervated by sympathetic ends that store dopamine (DA) (12,13).…”
Section: Endritic Cells (Dcs) Are the Most Efficient Type Of Apcsmentioning
confidence: 88%
“…Clearly there is evidence that cyclic AMP and mGluR interact because a given G protein has the potential to act through a network of multiple overlapping messengers (Neves, Ram et al 2002). Several lines of evidence support the view that mGluR and cAMP mediated pathways interact in platelets (Moos and Goldberg 1988), lymphocytes (Pacheco, Ciruela et al 2004), neurons (Otte, van Run et al 1989;Pilc, Legutko et al 1996;Cartmell, Schaffhauser et al 1997;Azad, Monory et al 2004;Warwick, Nahorski et al 2005) and astrocytes (Balazs, Miller et al 1998). This means that the impaired cAMP signaling in the cAMP theory of FX could be related to the Gq signaling described in the mGluR theory.…”
Section: Cyclic Amp Theory Of Fragile Xmentioning
confidence: 95%
“…[103][104][105] Glutamate receptors are differentially expressed in activated versus naïve T-cells, and are believed to contribute to T-cell development and regulation. 106 In addition, glutamate can augment the production of cytokines by lymphocytes, as well as their migratory ability. 107,108 GABA receptors appear to have an inhibitory function on immune responses in a subset of lymphocytes, 109 but may also increase pathogen clearance by macrophages.…”
Section: Neurotransmittersmentioning
confidence: 99%